Editorial - Editor (Hamdard Islamicus, 2021)
This issue has various articles on Qur’Énic doctrines, ethics and Islamic values, Islamic architecture, Islamic law and Divine books. “Communication Ethics from the Qur’Énic Perspective: An Analysis of Selected Contemporary Exegeses” from Malaysia provides a study on the ethics of dialogue and communication to others as embodied in the Holy Qur’Én, based in the most appropriate manner in exegetical writings while dealing with others. The next study from U.K. discusses “Zandaqah Heresy during the Early ‘AbbÉsid Era (750-850 C.E.)” in the Light of Socio-political and Economic Factors.